2019
DOI: 10.1089/ars.2017.7415
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial NAD+/NADH Redox State and Diabetic Cardiomyopathy

Abstract: Specific therapies must be supported by an optimal understanding of changes in mitochondrial redox state and how it influences other cellular compartments; this field has begun to surface as a therapeutic target for the diabetic heart. We propose an approach based on an alternate mitochondrial electron transport that normalizes the mitochondrial redox state and improves cardiac function in diabetes. Antioxid. Redox Signal. 00, 000-000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 205 publications
(275 reference statements)
2
103
0
Order By: Relevance
“…The NAD + /NADH ratio indicates the activity of various metabolic pathway enzymes, such as those involved in mitochondrial oxidation as the predominant energy source. Notably, a previous study demonstrated that a decreased NAD + /NADH ratio was associated with diabetic cardiomyopathy [23]. Our results revealed that mice transplanted with PAI-1KO scWAT had a significantly increased NAD + / NADH ratio in cardiac tissues compared with that in the WT and sham groups, suggesting that targeting PAI-1 is necessary for preventing the metabolic complications caused by obesity and T2DM.…”
Section: Discussionsupporting
confidence: 57%
“…The NAD + /NADH ratio indicates the activity of various metabolic pathway enzymes, such as those involved in mitochondrial oxidation as the predominant energy source. Notably, a previous study demonstrated that a decreased NAD + /NADH ratio was associated with diabetic cardiomyopathy [23]. Our results revealed that mice transplanted with PAI-1KO scWAT had a significantly increased NAD + / NADH ratio in cardiac tissues compared with that in the WT and sham groups, suggesting that targeting PAI-1 is necessary for preventing the metabolic complications caused by obesity and T2DM.…”
Section: Discussionsupporting
confidence: 57%
“…The NAD + /NADH ratio is a sensitive marker of the cellular redox state [93]. In fact, ROS production by activity of complex I depends on the matrix redox potential, and as a consequence, the increase in NAD + /NADH triggers PGC-1α deacetylation through SIRT1 activation [94].…”
Section: Tissue-specificmentioning
confidence: 99%
“…Besides, exercise improves glucose metabolism in the diabetic myocardium and pancreas. Long-term regular exercise has been shown to decrease nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, increase nitric oxide synthase and nitric oxide production, and enhance anti-oxidative activity in the endothelial cells [73]. The nuclear factor erythroid 2-related factor 2 (Nrf2) is crucial for defending cardiomyocytes against intracellular oxidative stress, and as a regulator of antioxidant response elements [74][75][76][77][78].…”
Section: Oxidative Stress In Cardiomyocytesmentioning
confidence: 99%